Urinary concentrations of AICAR and mannitol in athlete population. Issue 3 (4th January 2019) - Sobolevsky, Tim; Ahrens, Brian
Abstract: Both AICAR and mannitol are prohibited for use in sports, but no decisive criteria that would guide anti‐doping laboratories on data interpretation have been established so far. In an attempt to help harmonize reporting and management of analytical findings, reference population data collected for US athletes are presented. Upon analysis of 12 377 samples, mean urinary AICAR concentration was found to be 647 ± 365 ng/mL with median value of 574 ng/mL, 99th percentile at 1786 ng/mL and 99.7th percentile at 2151 ng/mL. Based on these results, we suggest that any sample with AICAR concentration greater than 2000 or 2500 ng/mL be analyzed by carbon isotope ratio mass spectrometry to establish the origin. Urinary mannitol concentrations demonstrate larger variation with the mean value of 72 ± 140 μg/mL and median at 41 μg/mL ( n = 6407). While the 99.7th percentile for mannitol was measured to be 1094 μg/mL, the population data alone is not sufficient to suggest a threshold value. It is also shown that the use of mannitol as a sweetener in amounts of up to 20 g per day results in a urinary concentration of about 14 mg/mL. As only intravenous mannitol is prohibited in sports, controlled excretion studies are needed to see whether intravenous administration could in fact be discriminated from dietary intake. An important observation is that mannitol present in mg/mL quantities significantly increases urine specific gravity, which makes a widely accepted normalization approach not applicable. Abstract : Mean urinary concentration of AICAR in reference population of US athletes is 647 ± 365 ng/mL, with median, 99th and 99.7th percentile being at 574, 1786, and 2151 ng/mL, respectively. We suggest that carbon isotope ratio mass spectrometry analysis be required for samples eceeding 2000 or 2500 ng/mL threshold. For mannitol, population data itself cannot justify a threshold, and controlled ecretion studies are needed to demonstrate whether intravenous administration could be discriminated from dietary intake, which may not be the case.